Impacts of dietary zinc on growth performance, haematological indicators, transaminase activity and tissue trace mineral contents of soft‐shelled turtle (Pelodiscus sinensis). (30th September 2021) - Kou, Hongyan; Hu, Junru; Wang, An‐Li; Pan, Xunbin; Miao, Yutao; Lin, Li
Abstract: A 12‐week growth trial was conducted to investigate the impacts of dietary zinc on growth performance, whole‐body composition, haematological parameters, liver aspartate aminotransferase and alanine transaminase activity and tissue trace mineral contents of soft‐shelled turtle ( Pelodiscus sinensis ). Approximately 4 g of turtles were fed fishmeal‐based diets with 35.43, 46.23, 55.38, 66.74, 75.06 and 85.24 mg Zn/kg. Respiratory burst, red blood cells and intestine somatic index enhanced with escalating dietary Zn concentrations up to 55.38 mg/kg and then kept constant beyond this level. Escalating dietary Zn inclusion up to 66.74 mg/kg improved weight gain, survival rate, feed intake, albumin, haemoglobin, liver aspartate aminotransferase and alanine transaminase activity, carapace ratio and crude protein of turtles, beyond which they decreased. Osmolality, hepatosomatic index and crude lipid of turtles firstly declined with elevating dietary zinc levels from 35.43 to 55.38 mg/kg diet and then increased at a higher zinc level. Liver and muscle Zn concentrations enhanced with escalating dietary zinc inclusion, whereas Cu and Fe concentrations reduced. In summary, the optimal dietary zinc requirements for turtles were 61.27, 60.46 and 60.03 mg/kg diet, based on quadratic regression analysis derived from weight gain, aspartate aminotransferase and alanine transaminase activity, respectively.